Norman Wells: The Oil Center of the Northwest Territories - Bone, Robert M.; Mahnic, Robert J. (ARCTIC, 1984)
In 1920, a drilling team funded by Imperial Oil discovered a petroleum deposit along the shore of the Mackenzie River north of the settlement of Fort Norman. This wilderness site later became the community of Norman Wells and its growth has been directly attributable to petroleum. The current expansion of production at Norman Wells is aimed at southern Canadian markets and a pipeline is being constructed from Norman Wells to existing pipelines in northern Alberta. As the focal point of this major resource expansion, the character, size, and functions of the community are changing. These changes are transforming Norman Wells into an important regional center.Key words: Norman Wells, petroleum development Mots clés: Norman Wells, l'expoitation du pétrole